Understanding the Women’s Role as Agriculture Laborers and Their Participation in Agriculture Economy: Examining the Impact of Women's Role as Agriculture Laborers on Economic and Social Development (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Agriculture represents very nearly 60 of total employment in India which is, overall, rural-based. It is discouraging to take note of that in the rural part the growth rate of agricultural employment is abysmally low. Rural workers in agriculture establish the biggest segment of India's work drive. Without any critical land change measures, a vast area of the rural work drive is landless and resource poor. Outrageous centralization of land possession and use perseveres even today. Illiteracy, absence of schooling, poor states of wellbeing and sanitation and malnourishment keep on being critical issues that haunt Indian villages. Agriculture is the critical area of any nation which is the fundamental requirement for the flourishing and nation’s growth. The agriculture segment is the economy’s foundation in the developing nations, which supply food and give employment to most of the populace. Agriculture not just give raw material to the industrial part yet additionally fill in as a market for its items and is thusly associated with all-around development of the nation. The world has seen the life and administrations of female agricultural laborers who have contributed a lot to the advancement and prosperity of the societies, countries and the world everywhere in the cultural, economic, and social otherworldly fields. In this Article we studied the Women’s role Agriculture Laborers and their Participation in Agriculture Economy